Pengenalan Manajemen Investasi dan Pasar Modal Bagi Masyarakat Migran Indonesia Di Malaysia - Bhilawa, SE, Ak, M.Si, CA, Loggar; Hariyati, Hariyati; Satyawan, Made Dudy; Laksono, Bayu Rama (Abimanyu : Jornal of Community Engagement, 2024)
The purpose of this service activity is to provide education and assistance to the community, especially Indonesians residing in Malaysia, on the importance of investing part of their income and provide educational training on one form of investment, namely the capital market. This means that upon returning from overseas, PMI can become entrepreneurs and develop the family economy independently. Even if the capital obtained is sufficient, without family encouragement and sufficient financial management skills, it will not encourage migrant workers not to return to migrate. The skills to build a business by looking at potential, opportunities, capital, management, and good prospects will be very much needed for PMI in the homeland. Strong financial planning and adequate management skills make obstacles in development for the long term in terms of finance optimally mitigated. The specific target through this mentoring and training is that each partner will be able to know the importance of investing compared to saving, change the paradigm of saving society to investment society, and become an individual investor to increase the wealth and economy of the partner's family in the future. The methods that will be used in achieving these goals are tutorials, training on the introduction of the capital market, as well as training and mentoring on how to trade stocks, choose stocks, determine good and bad stocks, stock trading strategies, and maintain the psychological stability of an individual investor. Keywords: investment, capital market, mentoring, PMI, Malaysia